Flexural behaviour of reinforced fly ash and paper sludge ash-based geopolymer concrete beams - Senthamilselvi, P.; Palanisamy, T. (Journal of Structural Engineering, 2024)
The present study aims at investigations of the flexural behaviour of reinforced Fly Ash (FA) Based Geopolymer Concrete (GPC) and fly ash and Paper Sludge Ash (PSA) based geopolymer concrete beams (FA-PSA-GPC) with 10% replacement of FA by PSA. The beams were made of M35 grade concrete and cured under three curing conditions viz., Ambient Curing (AC), External Exposure Curing (EEC) and Oven Curing (OC) at 60°C. The beams were tested at 28ᵗʰ day by conducting two-point loading flexural test. Performance aspects such as Load Carrying Capacity (LCC), First Crack Load (FCL), load-deflection behaviour, and moment–curvature behaviour of both types of beams were studied. The load-deflection and moment–curvature behaviours of two types of beams observed from the experimental results under different curing conditions were compared and it was concluded that GPC can be produced using PSA with FA.